2018
DOI: 10.1007/s10762-018-0498-y
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Characterization of Common and Exotic Filaments for Use in 3D Printed Terahertz Devices

Abstract: Recent years have seen an influx of applications utilizing 3D printed devices in the terahertz regime. The simplest, and perhaps most versatile, modality allowing this is Fused Deposition Modelling. In this work, a holistic analysis of the terahertz optical, mechanical and printing properties of 17 common and exotic 3D printer filaments used in Fused Deposition Modelling is performed. High impact polystyrene is found to be the best filament, with a useable frequency range of 0.1-1.3 THz, while remaining easily… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 43 publications
(46 reference statements)
1
19
0
Order By: Relevance
“…Although PP has been reported as difficult to use thermoplastic for ME‐AM due to the aforementioned warpage issues, 3D‐printed PP has been widely used in specific applications such as in applied chemistry. For instance, Gordeev et al .…”
Section: Potential Applications For 3d‐printed Ppmentioning
confidence: 99%
See 1 more Smart Citation
“…Although PP has been reported as difficult to use thermoplastic for ME‐AM due to the aforementioned warpage issues, 3D‐printed PP has been widely used in specific applications such as in applied chemistry. For instance, Gordeev et al .…”
Section: Potential Applications For 3d‐printed Ppmentioning
confidence: 99%
“…Other studies that revealed PP's potential as an engineering material with excellent stability against chemicals include the production of chemical process laboratories or chemical reaction vessels, for example, for the synthesis of bicyclic and tetracyclic heterocycles, the anti‐inflammatory drug ibuprofen, or multistep organic syntheses, the production of microfluidic devices for the medical and chemical industry, the fabrication of tailored reactor devices for mass spectrometry, or reactionware devices for continuous‐flow organic reactions . Additionally, various researchers recommended the use of 3D‐printed PP for various promising applications, such as for a chemically resistant laboratory equipment for the processing of semiconductors, for terahertz devices, or for a cheap and light weight alternative for the electrolysis of water …”
Section: Potential Applications For 3d‐printed Ppmentioning
confidence: 99%
“…1(d), respectively. The absorption coefficient of this material is higher than any other printable plastic tested until now [7]. The highly dispersive behavior of the refractive index is caused by the presence of carbon black in the PLA host.…”
Section: Design and Fabricationmentioning
confidence: 75%
“…Print settings were chosen to give a nozzle temperature of 220ºC, bed temperature of 50ºC and print speed of 80 mm/s. To retrieve the optical properties of CPLA, a 0.22 mm thick solid disk was printed and tested using THz transmission spectroscopy in a set up similar to the one used by Squires et al [7]. The refractive index and absorption coefficient of CPLA are shown in Fig.…”
Section: Design and Fabricationmentioning
confidence: 99%
See 1 more Smart Citation